The Amish - Kraybill, Donald B.; Johnson-Weiner, Karen; Nolt, Steven M., 1968- (Baltimore : Johns Hopkins University Press, 2013)
The Amish have always struggled with the modern world. Known for their simple clothing, plain lifestyle, and horse-and-buggy mode of transportation, Amish communities continually face outside pressures to modify their cultural patterns, social organization, and religious world view. An intimate portrait of Amish life, The Amish explores not only the emerging diversity and evolving identities within this distinctive American ethnic community, but also its transformation and geographic expansion.
Roots. Who are the Amish? ; European origins ; The story in America -- Cultural context. Religious roots ; Sacred rituals ; The Amish way ; Symbols and identity -- social organization. Diverse affiliations ; Population patterns ; Community organization ; Gender and family ; From Rumspringa to marriage ; Social ties and community rhythms ; Education -- External ties. Agriculture ; Business ; Technology ; Health and healing ; Government and civic relations ; The Amish in print ; Tourism and media -- The future. Pursuits of happiness -- Appendix A. Related groups : Mennonites, Brethren, Hutterites -- Appendix B. Key events in Amish history.
"The companion to American Experience PBS"--Jacket.
Includes bibliographical references (pages 461-485) and index.
Keywords: Amish -- Social life and customs; Amish -- History